Comparison of anti-inflammatory mechanisms between doxofylline and theophylline in human monocytes. (December 2019) - Talmon, Maria; Massara, Erika; Brunini, Chiara; Fresu, Luigia Grazia
Abstract: Background: Methylxanthines are important pharmacological agents in the treatment of asthma and of chronic obstructive pulmonary diseases. The present study was designed to compare the ability of doxofylline and theophylline to modulate inflammatory pathways in human monocytes. Methods: Monocytes isolated from healthy anonymous human buffy coats were treated with doxofylline or theophylline in the presence of phorbol 12-myristate 13-acetate (PMA) or lipopolysaccharide (LPS), and their phenotype, the oxidative burst, cytokine expression and release, cAMP production, and protein kinase C (PKC) activity were evaluated. Results: Doxofylline and theophylline did not have overlapping effects on human monocytes. While sharing some common characteristics, they differed significantly in their selectivity. Theophylline affected LPS- above PMA-induced cellular responsivity, while doxofylline behaved in the opposite manner. Furthermore, when testing PKC activity, we found an inhibitory effect of doxofylline but not of theophylline, at equimolar doses. Conclusions: In conclusion, our data support the growing hypothesis that doxofylline does not have a superimposable mechanism of action compared to theophylline, and this may both explain some differences in the risk/benefit ratio and may direct studies to tailor therapy for patients.